Internationalization of a Finnish SME specializing in engineering design : The significance of networks in Northern Sweden industrial markets - Polvi, Johanna Veera Juulia (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2024)
This thesis work studies the network model of internationalization for SMEs in the industrial sector, targeting challenges and strategies for expanding into international markets. The research aims to understand how SMEs can develop and leverage relationships within business networks to gain strategic advantages in international markets and how digital technologies can facilitate connection within niche industries such as forestry, wood, and battery production in Northern Sweden. The source of information for this study was retrieved from in-depth interviews that were held with experts with extensive experience in either international industrial sector and/or internationalization, networks, and networking. The insights indicate that credibility and trust are the root in developing strong network ties. Particularly domestic network ties can be leveraged by bridging to boost company’s internationalization. For SMEs strategic partner selection and active relationship management seems effective to stay well-positioned within a network along with having an opportunity to leverage from these ties. Lastly, the dual nature of networking seems to enhance SMEs ability to connect with international networks, maintain and develop international relationships. The study contributes to theory by showcasing the multi-faceted nature of SME internationalization and addresses the significance of combining digital and traditional networking methods. Considering practical implications, the research offers the case company and similar SMEs actionable strategies and enhanced understanding of establishing credibility, engaging with domestic networks along with utilizing institutional agencies to facilitate international expansion. If a company like the case company adopts presented strategies, they can potentially overcome resource limitations and efficiently navigate the multi-dimensional situations of international markets, thus, aiming for successive growth and advantage against competitors.